2020
DOI: 10.1186/s12931-020-1319-0
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β pathway activation by idiopathic pulmonary fibrosis (IPF) fibroblast derived soluble factors is mediated by IL-6 trans-signaling

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a chronic and ultimately fatal disease characterized by a progressive decline in lung function. Fibrotic diseases, such as IPF, are characterized by uncontrolled activation of fibroblasts. Since the microenvironment is known to affect cell behavior, activated fibroblasts can in turn activate healthy neighboring cells. Thus, we investigated IPF paracrine signaling in human lung fibroblasts (HLFs) derived from patients with IPF. Methods: Primary human fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 49 publications
3
69
0
Order By: Relevance
“…Both targets were found to be down-regulated in IPF patient samples. Supporting these results, our recent work, showed that the IL-6R protein level is also reduced in tissue samples taken from IPF patient biopsies [ 14 ]. A recent study by Wu et al [ 13 ], suggested that Cdc42 is an important post-transcriptional regulator that may play a significant role in the process of inflammation.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Both targets were found to be down-regulated in IPF patient samples. Supporting these results, our recent work, showed that the IL-6R protein level is also reduced in tissue samples taken from IPF patient biopsies [ 14 ]. A recent study by Wu et al [ 13 ], suggested that Cdc42 is an important post-transcriptional regulator that may play a significant role in the process of inflammation.…”
Section: Discussionsupporting
confidence: 58%
“…To date, limited targets of miR-608 have been confirmed in-vitro, and were mostly performed in tumor cell lines [ 32 ]. Our study focused on two targets that were previously implicated in IPF, IL-6 and Cdc42 [ 13 , 14 ]. Both targets were found to be down-regulated in IPF patient samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that CCL18 is associated with the progression and mortality in both SSc and IPF [ 12 , 14 ], the association of M2 macrophage phenotype with stat3 signaling in patients suffering from various types of pulmonary fibrosis including IPF may provide a molecular mechanism for CCL18 in fibrotic lung diseases [ 31 ]. In a recent study, the effect of IL-6 expression on TFG-ß related signaling pathways (STAT3, Smad3) in human lung fibroblasts derived from IPF patients could be antagonized by tocilizumab [ 32 ]. It is thus conceivable that inhibition of TGF-ß related signaling may also downregulate M2-macrophage activation and CCL18 expression.…”
Section: Discussionmentioning
confidence: 99%